Hungarian Monitoring, 8 May 1989 . [Magyar rádiófigyelő], 1989. május 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Before the Shevardnadze-Baker meeting - Most secret Soviet fighter plane presented in France - West German government denies that it has transported a missile factory to Romania - Opposition paper appears on the streets of Warsaw Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee session decides on relieving János Kádár and personnel changes - Hungarian Academy of Sciences general assembly opens - Hungary receives special invitee status to parliamentary sitting of Council of Europe - Alliance of Young Democrats (Fidesz) delegation in London - Liberal International delegation meets with SZDESZ - Austrian Chancellor in talks in America about Hungary - Hungary's renewal in crisis circumstances is an illusion, writes Viennese paper Die Presse Economy: - New law in preparation on private enterprises to dismantle all prior existing restrictions Külpolitika: - Sevardnadze-Baker találkozó előtt - Franciaországban bemutatták a legtitkosabb szovjet harci repülőgépet - A nyugatnémet kormány cáfolja, hogy rakétagyárat szállított Romániának - Ellenzéki napilap jelent meg Varsó utcáin Belpolitika: - MSZMP KB ülés, amelyen Kádár János fölmentéséről és személyi változásokról is döntöttek - MTA közgyűlés megnyitó - Magyarország különleges meghívotti státuszt kapott az Európa Tanács parlamenti ülésére - FIDESZ küldöttség Londonban - A Liberális Internacionálé küldöttségének találkozója az SZDSZ-el - Az osztrák kancellár Amerikában Magyarországról tárgyalt - Csak látszat a válság körülményei között Magyarország megújulása, - Írja a bécsi Die Presse Gazdaság: - Új törvény készül a magánvállalkozásról, amely minden eddigi korlátot lebont majd